Comparison of the basic principles of the green and sustainable chemistry concepts and the practice of their application - Stetsenko, Natalia (My University, 2025)
The scientific direction of "green chemistry" aims to prevent the negative impact of chemicals on the environment and human health at the initial stages of chemical processes by reducing or completely eliminating the use of hazardous chemicals or improving the synthesis processes that produce these chemical substances. “Sustainable chemistry” is a broader concept than “green chemistry” in terms of maintaining a balance between the needs of society in the present and the need to protect the environment in the future. Sustainable chemistry is a scientific concept that aims to increase the efficiency of the use of natural resources to meet human needs for chemical products and services. Sustainable chemistry includes the development, production and use of effective, efficient, more environmentally friendly chemical products and processes. The application of the basic approaches and principles of two concepts – green and sustainable chemistry – in the formation and development of chemistry, chemical technology and other industries is a driver of sustainable industrial development.

Науковий напрямок «зеленої хімії» спрямований на запобігання негативному впливу хімічних речовин на навколишнє середовище та здоров'я людини на початкових етапах хімічних процесів шляхом зменшення або повного виключення використання небезпечних хімічних речовин або вдосконалення процесів синтезу, що утворюють ці хімічні речовини. «Стала хімія» – це ширше поняття, ніж «зелена хімія», з точки зору підтримки балансу між потребами суспільства у поточний час та необхідністю захисту навколишнього середовища в майбутньому. Стала хімія – це наукова концепція, яка спрямована на підвищення ефективності використання природних ресурсів для задоволення потреб людини в хімічних продуктах та послугах. Стала хімія включає розробку, виробництво та використання ефективних, більш екологічно чистих хімічних продуктів та процесів. Застосування основних підходів та принципів двох концепцій – зеленої та сталої хімії у хімічних технологіях та інших галузях промисловості є рушійною силою сталого промислового розвитку.
Keywords: green chemistry; sustainable chemistry; environment; chemical substances; sustainable development; principles of sustainable chemistry; зелена хімія; стала хімія; навколишнє середовище; хімічні речовини; сталий розвиток; принципи сталої хімії; кафедра технології оздоровчих продуктів